What you need to know about occupational exposure to metalworking fluids - USA. National Institute for Occupational Safety and Health (Cincinnati, 1998)
"This document contains a critical review of the scientific and technical information available on the extent and type of health hazards associated with metalworking fluids and the adequacy of control methods."